Participatory seed projects and agroecological landscape knowledge in Central America - Megan D. Baumann; Karl S. Zimmerer; Jacob van Etten (International Journal of Agricultural Sustainability, 2020)
Participatory projects supporting the farmer-based seed management of agrobiodiverse varieties including landraces have proliferated globally in response to nutritional insecurity and climate change. This research examines the agroecological landscape knowledge of farmers in a recent participatory seed project using the tricot approach in Central America. Over 800 smallholder farmers in Nicaragua facilitated on-farm trials of diverse common bean varieties that are nutritiously valuable and potentially well-adapted to increased temperatures and variable precipitation. Our article integrates relevant research concepts in a case study of the agroecological landscape knowledge of 52 participating farmers. Participatory sketch maps, transect walks, and semi-structured interviews were used to identify key areas of farmers’ agroecological landscape knowledge in crop and seed management. Results indicate the prevalence of nine themes of farmer agroecological landscape knowledge. This landscape knowledge exerts major influence on the choice, placement, and management of common bean varieties and associated land use decisions. Our analysis reveals that farmers use this knowledge to manage their landholdings as landscapes of agroecological interactions that guide seed and variety management and affect potential sustainability. Results demonstrate that local agroecological landscape learning is strengthened through and benefits participatory seed projects.